CuCN-Mediated cascade cyclization of 4-(2-bromophenyl)-2-butenoates: a high-yield synthesis of substituted naphthalene amino esters - Reddy, R. Santhosh; Prasad, Pragati K.; Ahuja, Brij Bhushan; Sudalai, Arumugam (Journal of Organic Chemistry, 2013)
A new method of CuCN-mediated one-pot cyclization of 4-(2-bromophenyl)-2-butenoates leading to efficient synthesis of substituted naphthalene amino esters including phenanthrene aromatic structural units is described. Deuterium labeling studies establish that this one-pot cascade cyclization proceeds through isomerization of olefin, intramolecular C-C bond cyclization, and aromatization as the key intermediates, all occurring in a single step.